Estrogen receptor variant ER-α36 is involved in estrogen neuroprotection against oxidative toxicity. (3rd December 2015) - Han, S.; Zhao, B.; Pan, X.; Song, Z.; Liu, J.; Gong, Y.; Wang, M.
Highlights: ER-α36 is involved in estrogen neuroprotection. ER-α36 is involved in rapid activation of the PI3K/AKT and MAPK/ERK signaling pathways in estrogen neuroprotective effect. GPER (GPR30) is not involved in ER-α36-mediated rapid estrogen response. Abstract: It is well known that estrogen exerts neuroprotective effect against various neuronal damages. However, the estrogen receptor (ER) that mediates estrogen neuroprotection has not been well established. In this study, we investigated the potential receptor that mediates estrogen neuroprotection and the underlying molecular mechanisms. Hydrogen peroxide (H2 O2 ) was chosen as an agent in our study to mimic free radicals that are often involved in the pathogenesis of many degenerative diseases. We found that in human SY5Y and IMR-32 cells, the estrogen neuroprotection against H2 O2 toxicity was abrogated by knockdown of a variant of estrogen receptor-α, ER-α36. We also studied the rapid estrogen signaling mediated by ER-α36 in neuroprotective effect and found the PI3K/AKT and MAPK/ERK1/2 signaling mediated by ER-α36 is involved in estrogen neuroprotection. We also found that GPER, an orphan G protein–coupled receptor, is not involved in ER-α36-mediated rapid estrogen response. Our study thus demonstrates that ER-α36-mediated rapid estrogen signaling is involved in the neuroprotection activity of estrogen against oxidative toxicity.